Akibat Pembatalan Hukum Hibah dan Penghapusan Nasab (Studi Kasus Perkara Nomor : 241/Pdt.G/2024/PA. Kab Malang) - Jadidah, Amatul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract In Dutch, the term for hibah (grant) is schenking, which refers to the act of giving by one person to another without expecting anything in return, done while the giver is still alive and irrevocable. This grant is transferred to benefit the recipient. In substance, the existence of hibah is closely related to inheritance. This is explicitly stated in Indonesia’s positive law, such as the Compilation of Islamic Law (CIL), customary law, and the Civil Code. Additionally, there is the possibility of revoking a hibah already given, as explained in the Compilation of Islamic Law, customary law, and the Civil Code, as stipulated in Article 1666. Hibah is often conducted while the giver is still alive to avoid disputes among their children after passing away. This could stem from concerns due to the children’s mother being a stepmother or foster mother or because among the children, there is an adopted child whose status as an heir might be contested. According to the provisions of Article 210(1) of the Compilation of Islamic Law, a person granting a hibah must be at least 21 years old, mentally sound, and act without coercion. They can grant up to one-third of their assets to another person or institution in the presence of two witnesses. One of the legal ways to transfer ownership in Islamic law, besides inheritance and sale, is through hibah. By granting an asset, the ownership transfers from the giver (wahib) to the recipient (mawhub lah). Islam encourages generosity as it fosters warmth and affection among people and strengthens familial ties, which is a fundamental teaching of Islam. Keywords: Grant (Hibah) Inheritance Legitime Portie Family Dispute Abstrak Hibah merupakan salah satu bentuk pemberian yang memiliki implikasi hukum signifikan, terutama dalam konteks kewarisan di Indonesia. Studi ini berfokus pada kekuatan hukum pembuktian surat hibah bersegel tahun 1967 terkait tanah pertanian yang menjadi objek sengketa di Pengadilan Agama Kepanjen dengan nomor perkara 24/PA/KPjn/2023. Dalam penelitian ini, dibahas dinamika sengketa hibah yang melibatkan ahli waris kalalah dan cucu angkat, di mana penggugat menggugat keabsahan hibah yang diberikan oleh pemberi hibah kepada cucu angkatnya. Penelitian ini menggunakan pendekatan yuridis normatif dengan metode deskriptif analitis untuk menganalisis regulasi yang relevan, termasuk Kompilasi Hukum Islam, Kitab Undang-Undang Hukum Perdata, dan peraturan terkait pendaftaran tanah. Data penelitian diperoleh melalui studi dokumen hukum serta wawancara dengan pihak terkait, seperti penggugat, hakim, mediator, dan Badan Pertanahan Nasional. Hasil penelitian menunjukkan bahwa surat hibah bersegel memiliki kekuatan hukum sepanjang memenuhi ketentuan formal dan materiil, namun dalam praktiknya sering menjadi objek sengketa apabila dianggap merugikan ahli waris lainnya. Selain itu, ditemukan bahwa legitimasi hibah dapat dipertanyakan apabila tidak sesuai dengan ketentuan legitime portie sebagaimana diatur dalam Pasal 920 KUHPerdata. Kata Kunci: Hibah Pewarisan Legitime Portie Sengketa Keluarga